Legal Certainty Of The Rights Of Children Born Out Of Wedlock To Their Biological Fathers - Wahyu Fitria, Nabila; Suryono, Arief; Saptanti, Noor (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2024)
Children are both a divine gift and a solemn duty bestowed by the Supreme Being. Law Number 1 of 1974, which has been amended by Law Number 16 of 2019 concerning Amendments to Law Number 1 of 1974 concerning marriage, distinguishes between two categories of child status. Article 2 pertains to legitimate children, while Article 43 addresses children born out of wedlock. Illegitimate children are commonly used to refer to children born outside of marriage in a broader context. They are born due to a extramarital relationship between a woman and a man. The relationship between the two is biological, without legal recognition, such as a marriage officially registered by the state. Facing issues surrounding the existence of illegitimate children, According to Article 43 of Law Number 1 of 1974, which has been amended by Law Number 16 of 2019 concerning Amendments to Law Number 1 of 1974 concerning marriage, it is stated that individuals do not possess a formal legal bond with their biological father. The impact is that they do not receive financial security, education, or inheritance rights. In addition, society tends to assess children born out of marriage negatively, considering them different from legitimate children. If the child is legally recognized as illegitimate, then the family relationship is civilly terminated; for the child, they are only bound to his mother. This situation causes discrimination against the legal entitlements of children born out of wedlock. This article explores legal clarity on the rights of children born from extramarital partnerships. The author uses a normative methodological approach in this research, utilizing secondary data and data collection strategies such as document studies, theoretical ideas, and existing principles. Data analysis in this research involves deductive analysis using a statutory approach and conceptual framework.